DESAIN OPTIMAL PONDASI MESIN BLOK TERTANAM AKIBAT BEBAN DINAMIS - Minson Simatupang; Sulha Sulha; Izzat Arif (Jurusan Teknik Mesin, Universitas Halu Oleo, 2019)
Design of machine foundation is differed with design of other foundations in general. It retains not only static loads but also dynamic loads deriving from machine vibrations. The structure of the foundation must be able to support both of those loads without any failure. This study presents the optimal design of the embedded block machine foundation that it is not only safe to the operation of the machine itself but also it is not disturb the equipment or the people in the vicinity. The data used are the machine’s data according to the factory specification, the soil investigation data at the foundation site obtained using a ground drilling machine, and laboratory data. Field data are as N-SPT data, soil type for each layer, and groundwater table. Desain and dynamic responses analysis of foundation used elastic half space method, and modeling of soil settlement used palaxis sofware. By using trial and error method, it is obtained optimal dimension of the machine foundation with a length of 4.6 m, 2.5 m wide, 0.8 m high, and 0.6 m embedded foundation depth. With these dimensions, proposed foundation is reliable against the machine operation without interferences to the sorrounding environment.